1974
DOI: 10.3758/bf03208990
|View full text |Cite
|
Sign up to set email alerts
|

An attribute frequency model for the abstraction of prototypes

Abstract: An attribute frequency model for the abstraction of prototypes is proposed as an alternative to the prototype-plus-transforrnation model. A specific model is tested in a Franks and Bransford visual pattern paradigm under conditions in which the two models generate contrasting predictions. The results support the attribute frequency model. Application of the model to reported data obtained in other paradigms is illustrated and discussed.Studies of concept formation have traditionally used concepts defmed by a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

9
83
0

Year Published

1977
1977
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(92 citation statements)
references
References 6 publications
(8 reference statements)
9
83
0
Order By: Relevance
“…There has been little investigation of factors affecting the acquisition of the original training items. In general, whether a schemaabstraction theory assumes that classification of novel items is based on similarity to stored instances (Medin & Schaffer, 1978), a central tendency or prototype (Franks & Bransford, 1971;Posner & Keele, 1968), or the frequency of feature and feature combinations during learning (Elio & Anderson, 1981;Hayes-Roth & Hayes-Roth, 1977;Neumann, 1974;Reitman & Bower, 1973), a default prediction seems to be that every study item encountered will have an equal impact on the final schema and this impact will be independent of exemplar presentation order.…”
mentioning
confidence: 99%
“…There has been little investigation of factors affecting the acquisition of the original training items. In general, whether a schemaabstraction theory assumes that classification of novel items is based on similarity to stored instances (Medin & Schaffer, 1978), a central tendency or prototype (Franks & Bransford, 1971;Posner & Keele, 1968), or the frequency of feature and feature combinations during learning (Elio & Anderson, 1981;Hayes-Roth & Hayes-Roth, 1977;Neumann, 1974;Reitman & Bower, 1973), a default prediction seems to be that every study item encountered will have an equal impact on the final schema and this impact will be independent of exemplar presentation order.…”
mentioning
confidence: 99%
“…The author wishes to thank Cheryl Berryman, Lisa Gemma, and Robert Ciulla for assistance in collecting the data. Requests for reprints should be sent to the author at: Department of Psychology, University of Maryland Baltimore County, Baltimore, Maryland 21228. of nonsense syllables (Katz & Gruenwald, 1974), letter and digit sequences (Reitman & Bower, 1973), and visual patterns Neumann, 1974). Katz (1973) has shown that the effect disappears when recognition instructions are modified and subjects are only required to judge whether recognition sentences have the same meaning as acquisition sentences.…”
mentioning
confidence: 99%
“…Katz, Atkeson, and Lee (1974) have shown that sentences consisting of a single idea are rated much higher when the acquisition list consists entirely of single-idea sentences, and they suggest, therefore, that the linear effect is an artifact of the method of presenting sentences of varying complexity during acquisition. These studies, taken together, suggest that the linear "linguistic" effect is a function of decision processes occurring during recognition rather than a function of semantic integration occurring during acquisition.Both Neumann (1974) and Reitman and Bower (1973) have pointed out that the Bransford-Franks paradigm is essentially a concept-formation task in which subjects are tested for recognition of the specific instances of a concept which were presented during acquisition. Although neither of these studies used linguistic stimuli, both demonstrated that a linear recognition function can be accounted for by a recognition model in which the recognition rating for a given item is a function of the frequency of presentation of its elements during acquisition, provided the recognition item contains no new elements.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Posner and Keele (1968), who showed that after learning a set of distorted patterns, human subjects could easily classify the prototype of the distorted patterns, proposed a prototype distance model to explain these interesting results. Other models, such as the attribute-frequency model (Neumann, 1974(Neumann, , 1977 and the category-density model (Fried & Holyoak, 1984), also predict abstraction of the prototype from its distorted derivatives.…”
mentioning
confidence: 99%